Analisis Morfosemantik Neologisme Teknologi Informasi Arab di Al Jazeera (2024) - Zainurrakhmah, Zainurrakhmah (Titian: Jurnal Ilmu Humaniora, 2024)
The rapid development of information technology (IT) has spurred the emergence of neologisms, including in the Arabic language. This study aims to morphosemantically analyze IT neologisms appearing in online news articles from Al Jazeera during January-October 2024. Employing a qualitative descriptive approach, data were collected via digital documentation using purposive sampling and analyzed based on six word-formation pattern categories from Al-Najjar’s (1989) framework: loanword, loanblend, translation couplet, derivation, calque (or loan translation), and semantic loan. The findings identified 26 IT neologisms, indicating that Arabic actively integrates new concepts by balancing global influences with its rich internal linguistic structure. Loanword and loanblend patterns accelerate the introduction of global terms; translation couplets bridge accessibility and conceptual clarity; while derivation, calque, and semantic loan play crucial roles in technological conceptualization, maintaining structural integrity and cultural relevance. The conclusion affirms that Arabic is a dynamic, adaptive, and productive system in addressing IT lexical innovation in the digital era. Abstrak Perkembangan pesat teknologi informasi memicu kemunculan neologisme, termasuk dalam bahasa Arab. Penelitian ini bertujuan menganalisis secara morfosemantik neologisme teknologi informasi (TI) yang muncul pada artikel berita daring Al Jazeera selama Januari-Oktober 2024. Menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui dokumentasi digital dengan teknik purposive sampling dan dianalisis berdasarkan enam kategori pola pembentukan kata dari kerangka Al-Najjar (1989): loanword (kata serapan), loanblend (campuran serapan), translation couplet (penerjemahan kuplet), derivation (derivasi), calque (saduran atau penerjemahan pinjam), dan semantic loan (pinjaman makna). Hasil penelitian mengidentifikasi 26 neologisme TI, menunjukkan bahasa Arab aktif mengintegrasikan konsep baru dengan menyeimbangkan pengaruh global dan kekayaan struktur internalnya. Pola loanword dan loanblend mempercepat pengenalan istilah global; translation couplet menjembatani aksesibilitas dan kejelasan konseptual; sementara derivasi, calque, dan semantic loan berperan krusial dalam konseptualisasi teknologi serta mempertahankan integritas struktural dan relevansi budaya. Simpulan menegaskan bahwa bahasa Arab merupakan sistem yang dinamis, adaptif, dan produktif dalam menghadapi inovasi leksikal TI di era digital.